The Illusion of Inclusion : Women's Access to Rights in Northern Kenya - Ayuko, Bonita; Chopra, Tanja (World Bank, Nairobi, 2013)
This paper shows how official laws concerning justice for women, can be difficult to apply when they are not socially acknowledged, contextualized, or received, and therefore have minimal impact on women's lives. It demonstrates that the inclusion of women through international conventions, domestic legal reform, and gender quotas in participatory processes, is illusory. While these are all important instruments in women's empowerment, the paper calls upon access to justice practitioners and policy makers to place equal emphasis on fostering the practical implementation of laws and to emphasize opportunities for increased equality in informal systems.